ANALISIS BIAYA MUTU ALAS KAKI MODEL BS-12 DI CV.XYZ - Hidayah, Nur Yulianti; Raldi, LD Muhammad (Teknik Industri Unikom, 2023)
CV.XYZ is a company that produces footwear. From December 2022 – February 2023, the BS-12 footwear model experienced many product rejects. The high percentage of rejected products raises quality costs for rework activities. Identification of the type of rejection and the rework process is needed to determine the rework costs incurred by the company. Analysis of quality costs due to the rework process was carried out using the Process Costing method while identifying the factors causing the occurrence of rejected products using Why-why Analysis. The results of the analysis showed that there were 6 types of damage, namely straps (mouldy, abrasions, broken seams), insole (mouldy, abrasions, broken seams), excess glue, less sticky insole and outsole, loose straps & slippery sole. The quality costs incurred by the company during December 2022 – February 2023 amount to IDR 16,250,104. Products were rejected for multiple reasons, including inadequate facilities and equipment, operators working from home, and a staff shortage to meet production demands. Proposed improvements using 5W+1H included rearranging the production layout for strap storage, making SOP and WI for operators who work at home, buying press machines, and increasing the number of operators.